2012
DOI: 10.1111/j.1469-8749.2012.04434.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of sensory processing in infants: a systematic review

Abstract: AIM The aim of the study was to evaluate the psychometric properties and clinical use of assessments of sensory processing function, within the first 2 years of life, and to identify which assessment is the most appropriate and precise in measuring the construct of sensory processing.METHOD The literature was comprehensively searched, and assessments used to measure sensory processing in infancy were systematically selected and reviewed for clinical use, reliability, validity, and responsiveness.RESULTS Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
77
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 33 publications
1
77
1
10
Order By: Relevance
“…Although an association between food selectivity and oral sensory sensitivity has been reported in children with autism spectrum disorders (40,41) and premature infants (42)(43)(44), it has not been examined often as a predictor of food selectivity or pickiness in typically developing children. The associations between atypical SBs, food neophobia, and food acceptance patterns are worthy of additional investigation in larger samples with more rigorous dietary intake measures and with the use of longitudinal designs.…”
Section: Discussionmentioning
confidence: 97%
“…Although an association between food selectivity and oral sensory sensitivity has been reported in children with autism spectrum disorders (40,41) and premature infants (42)(43)(44), it has not been examined often as a predictor of food selectivity or pickiness in typically developing children. The associations between atypical SBs, food neophobia, and food acceptance patterns are worthy of additional investigation in larger samples with more rigorous dietary intake measures and with the use of longitudinal designs.…”
Section: Discussionmentioning
confidence: 97%
“…In extensive meta-analysis of sensory modulation symptoms in persons with ASD, different versions of the sensory profile, including ITSP, were found to be the most frequently used methods for measuring sensory processing 35. Unlike M-CHAT and CSBS-DP-ITC, ITSP is not generally used for screening;36 however, early on we concluded that ITSP might be a useful screening tool because autistic children often display unusual behavioral responses to sensory input, such as hypersensitivity to auditory, visual, tactile, and olfactory stimuli 37,38. Our study may be the first to evaluate its use as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…The processing of information allows individuals to respond automatically, efficiently, and comfortably to the specific sensory inputs received (2, 3). The neurobiological process comprises a series of five stages, registration, modulation, discrimination, integration, and praxis (4), and is central to cognitive processes such attention, visual perception, memory, and planned action (5). …”
mentioning
confidence: 99%
“…Eeles et al report that SPDs may be the cause of learning and development difficulties found in some children (4). …”
mentioning
confidence: 99%
See 1 more Smart Citation